Next Generation Sequencing Reveals Pathogenic and Actionable Genetic Alterations of Soft Tissue Sarcoma in Chinese Patients: A Single Center Experience. (December 2021) - Jin, Gu; Wang, Chunyang; Jia, Dongdong; Qian, Wenkang; Yin, Chunming; Wang, Danhua; Yang, Quanyu; Li, Tao; Zheng, Aiwen
Background: Next generation sequencing (NGS) has systematically investigated the genomic landscape of soft tissue sarcoma (STS) in Western patients, but few reports have described the utility of NGS in identifying pathogenic and targetable mutations in Asian patients.Methods: We review our single center experience of identifying the genomic profile and feasible genetic mutations in 65 Chinese patients with STS by NGS.Results: On average, 3.35 mutations were identified per patient (range, 0-28), and at least one mutation could be detected in 95.4% (62/65) of patients. TP53, MDM2, CDK4, KDR, and NF1 were the most frequent mutation genes in Chinese STS patients. Actionable mutations were discovered in 36.9% (24/65) of patients, and clinical benefit was achieved in 4 patients treated with corresponding molecular targeted therapies.Conclusions: Our study describes the mutation profile of Chinese STS patients by a single center experience. Some patients have achieved improved clinical outcomes by adopting treatment based on the results of genetic testing. NGS may affect clinical decision-making as a routine clinical test for patients with STS.